Cuscuta reflexa Roxb. Poisoning: A Case Report - Prasad, Pravin; Bajracharya, Sangha R; Lamichhane, Samir; Ghimire, Rakesh; Gupta, Sanjay K; Prasad, Archana (Journal of Institute of Medicine Nepal, 2021)
Cuscuta reflexa (C. reflexa Roxb.), is an endogenous parasitic plant found in Nepal and has been used by various ethnic communities of Nepal. However, there has been cases of toxicity in humans which needs attention. Here we discuss a case of C. reflexa Roxb. Accidental self-poisoning while being used for liver ailments that presented with gastrointestinal symptoms initially and local health facility and visited two health facilities before presenting to Tribhuvan University Teaching Hospital with multiple complaints. Appropriate risk assessment was done and the patient was managed conservatively at our center for three days following which he was discharged.